2015
DOI: 10.1074/jbc.m114.597377
|View full text |Cite
|
Sign up to set email alerts
|

The Src Homology and Collagen A (ShcA) Adaptor Protein Is Required for the Spatial Organization of the Costamere/Z-disk Network during Heart Development

Abstract: Background:The Src homology and collagen A (ShcA) adaptor protein plays a crucial role in heart development but the underlying mechanisms are unknown. Results: Early conditional deletion of ShcA in cardiomyocytes leads to heart failure with abnormalities in the costamere/Z-disk network. Conclusion: ShcA protects against heart failure by maintaining costameres/Z-disk axis integrity. Significance: Understanding molecular mechanisms involved in heart failure may help to develop new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…We generated Tie2Cre+/ShcA flox/flox mice, in which ShcA is selectively ablated in endothelial cells, by inter-crossing Tie2Cre transgenic mice with floxed ShcA animals 13 (ShcA flox/flox ). To increase atherosclerosis susceptibility, Tie2Cre+/ShcA flox/flox animals were maintained on a LDL receptor-deficient background (LDLR−), fed an atherogenic diet, and are hereafter referred to as endoShcA-.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We generated Tie2Cre+/ShcA flox/flox mice, in which ShcA is selectively ablated in endothelial cells, by inter-crossing Tie2Cre transgenic mice with floxed ShcA animals 13 (ShcA flox/flox ). To increase atherosclerosis susceptibility, Tie2Cre+/ShcA flox/flox animals were maintained on a LDL receptor-deficient background (LDLR−), fed an atherogenic diet, and are hereafter referred to as endoShcA-.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it does not indicate in which vascular cell type ShcA deletion would be atheroprotective. We previously reported that the deletion of ShcA in vSMCs did not modify the development of atherosclerotic lesions in mice fed an atherogenic diet 13 . Here, to study the role of ShcA in atherosclerosis and vascular remodeling, we suppressed its expression specifically in endothelial cells using the Cre/lox system.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…C57/B6 mice carrying a ShcA allele into which loxP sites are integrated have been generated by gene targeting in embryonic stem cells. LoxP sites have been introduced upstream of exon 2 and downstream of exon 7 (ShcA flox/flox ) (16). Cre-mediated recombination resulted in deletion of a 2-kb fragment containing the sequence encoding the PTB domain required for binding to phosphorylated receptors and for signaling activity.…”
Section: Methodsmentioning
confidence: 99%
“…We generated TwShcA-mice in which ShcA is selectively ablated in chondrocytes by breeding Twist2 transgenic mice with ShcA flox/flox mice (16). In TwShcA-mice, the three isoforms of ShcA were efficiently reduced in chondrocytes isolated from knee articular cartilage, vertebral and costal cartilage but not in non-cartilaginous tissues like lungs or the spleen (supplemental figure A and B).…”
Section: Specific Deletion Of Shca In Chondrocytes Leads To Dwarfismmentioning
confidence: 99%